Relações entre desempenho e o reforçador das relações verbais de tato e textual em contexto de equivalência de estímulo - Guimarães, Luiza de Moura (2012)
In some conditions, verbal relations of tact which involves nonverbal stimuli, such as pictures, exhibit characteristics and maintenance of learning different from textual relations, which are controlled by verbal products of verbal responses, such as printed words. These differences trigger practical interest in the teaching of reading when the stimuli that control such verbal operands belong to a single class, and are equivalent. It is assumed that in this proposal as the previous individual experience with each of relation, cannot be contacted directly but can be measured by their respective reinforcing value. The proposal presents a procedure to test this assumption, based on the establishment of stimulus classes involving equivalent relation with figure, printed and spoken words, tests of emergent relations of tact and textual and a procedure of choice in concurrent schedules chained. The aim of this study was to investigate whether the differences between the performances on tasks of tact response (oral response forward figure) and on tasks of textual behavior (oral response forward printed word) correlate with the preference of participants for such a task. In Experiment 1, six university students participated. In Experiment 2A and 2B finished the study four typically developing children without knowing reading repertoires. The general procedure began with the completion of two pre-tests, one requesting an oral responses to the stimuli and the second consisted of an evaluation preference for pictures versus printed words. After completion of the pre-tests, there was a matching procedure-tosample (MTS) for the establishment of equivalence relations. Stimuli were used: three spoken words (A), three figures (B) and three printed words (C). The set (A ') consisted of responses spoken by the participants, corresponding to the words dictated. During the MTS, were taught AB and AC relations, and were tested the emergence of relations BC, CB, BA '(tact) and CA' (textual). In Experiments 1 and 2A were used abstract figures and printed and spoken pseudo-words. In Experiment 2B were used familiar pictures of cow, duck and bell and their corresponding printed and spoken names. After established of equivalence classes, was carried out a procedure of choice in a concurrent schedule of reinforcement with chaining to evaluate preference for tasks. In this evaluation were presented two identical red buttons (Experiments 1 and 2A), or two buttons with icons of pictures and printed words (Experiment 2B) followed by the statement "which one you want?". Once the participant touched a button, a task of tact or a textual was presented. Touches on the right button were followed by the presentation of textual tasks (CA ') and touches on the left button were followed by tact tasks (BA'). If the participant showed preference for task, the position of the buttons was reversed. The results showed no correlation between the performance of tact and textual and preference for tasks. Moreover, the preference for tasks found, by some participants, showed that the establishment of equivalence relations may does not equal the reinforcing value of the tasks of these relations.